Comparison of microbial diversity and community structure in soils managed with organic and chemical fertilization strategies using amplicon sequencing of 16 s and ITS regions - Mishra, Ajay Kumar; Yadav, Poonam; Sharma, Sheetal; Maurya, Piyush (Frontiers in Microbiology, 2025)
Soil microbial species diversity and distribution of microbial communities are vital for soil and crop health, nutrient cycling, availability, and subsequent plant growth. These soil dynamics are highly influenced and altered by various soil management practices, inputs, and agricultural techniques. In the present study, the effects of chemical and organic management practices on soil microbial diversity and community structure were examined and compared using amplicon sequencing of the 16S and ITS regions. Two contrasting soil samples were selected from each crop fields at the International Rice Research Institute-South Asia Regional Centre (IRRI-SARC) in Varanasi: one field followed conventional chemical fertilizer inputs, while the other implemented natural farming practices, including tillage, on-farm crop residue management, and water management. Soil samples from each field were analyzed for bacterial and fungal diversity. Our findings showed that the two differently managed soils exhibited distinct microbial community compositions, with the organically managed soil exhibiting a higher diversity of decomposer bacteria and fungi, showing 40 unique elements in organic soil samples and 19 in chemically managed soil. Natural farming practices also demonstrated a higher relative abundance of bacterial and fungal phyla. Our results emphasize the significance of sustainable soil management techniques, suggesting that organic inputs can increase soil microbial diversity and richness. The functional roles of these microbial communities in soil ecosystems and their potential impact on crop yield and nutrient cycling warrant further study.